Bank risk exposures in the East Asian Region - Alireza Tamadonnejad,; Aisyah Abdul-Rahman,; Mariani Abdul-Majid,; Mansor Jusoh, (Penerbit Universiti Kebangsaan Malaysia, 2014)
Risk management is a pivotal factor for managing financial institutions. Efficient and sustainable banking activity requires managers to take all sources of instability into account and to adopt strategies against risks. The objective of the present paper is to investigate the sources of bank risks with a straightforward and comprehensive risk measurement for the East Asian region. The Z-risk index and a three-factor Capital Asset Pricing Model (CAPM) are adopted to estimate the probability of insolvency, systematic bank risks and unsystematic bank risks. The results demonstrate that banks in East Asian countries are exposed to a variety of risk exposures. Also, the findings show that banks with lower unsystematic risks do not necessarily have lower insolvency risks, indicating that the sources of insolvency risk are complicated and need further research. Finally, a regional cooperation strategy among banks is suggested so that exchange rate and interest rate risks can be reduced.